2018
DOI: 10.1093/nar/gky857
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a responsive DNA triple helix into an octahedral DNA nanostructure for a reversible opening/closing switching mechanism: a computational and experimental integrated study

Abstract: We propose an experimental and simulative approach to study the effect of integrating a DNA functional device into a large-sized DNA nanostructure. We selected, as a test bed, a well-known and characterized pH-dependent clamp-switch, based on a parallel DNA triple helix, to be integrated into a truncated octahedral scaffold. We designed, simulated and experimentally characterized two different functionalized DNA nanostructures, with and without the presence of a spacer between the scaffold and the functional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Binding of the allosteric remodeler induces a conformational change in the DNA nanostructure toward an opened conformation, represented in Figure 1F and highlighted in Figure 1D, for the face containing the hairpins. allow the transition from a "folded" to an "unfolded" form for the transport and release of triplexspecific binding molecules [13]. Tetrahedral DNA cages have been modified with the use of DNA oligonucleotides with pH-sensitive i-motif, to encapsulate an enzyme inside them [14].…”
Section: Models Of the Closed/opened States Of H4 Dna Nanocagementioning
confidence: 99%
See 1 more Smart Citation
“…Binding of the allosteric remodeler induces a conformational change in the DNA nanostructure toward an opened conformation, represented in Figure 1F and highlighted in Figure 1D, for the face containing the hairpins. allow the transition from a "folded" to an "unfolded" form for the transport and release of triplexspecific binding molecules [13]. Tetrahedral DNA cages have been modified with the use of DNA oligonucleotides with pH-sensitive i-motif, to encapsulate an enzyme inside them [14].…”
Section: Models Of the Closed/opened States Of H4 Dna Nanocagementioning
confidence: 99%
“…Sci. 2020, 21, 61 2 of 11 transition from a "folded" to an "unfolded" form for the transport and release of triplex-specific binding molecules [13]. Tetrahedral DNA cages have been modified with the use of DNA oligonucleotides with pH-sensitive i-motif, to encapsulate an enzyme inside them [14].…”
Section: Introductionmentioning
confidence: 99%
“…[248] Later they engineered the triplex structure into an octahedral DNA nanostructure for a reversible opening/closing switching. [249] They also promote electron transfer reaction by applying different voltage potentials on the surface of the electrode, releasing molecular input (metal ions or specific DNA sequences) from the electrode surface and triggering DNA-based nanoswitches or nanodevices. [45] DNA nano tweezers or scissors that respond to external stimuli have been widely developed as a class of nanoswitches with special configuration.…”
Section: Dna Nanomachinesmentioning
confidence: 99%
“…[9] Therefore, the stimuli-responsive system has undoubtedly become an ideal element for building DNA switches. [45,112,130,174,[244][245][246][247][248][249][250]273] For example, Yu's group reported a robust electronic switch made of immobilized ion-responsive peroxidase-mimicking DNAzyme, which could achieve switching operation under the action of K + and crown-6. [245] Fan's group reported the i-motif switch www.advancedsciencenews.com www.advancedscience.com realized by electrochemically controlling the pH of the solution.…”
Section: Dna Nanomachinesmentioning
confidence: 99%
“…[25] In this context, the full understanding of the DNA triplex-based devices' atomistic behavior represents an important aspect for a fine prediction of the rules governing their structure/dynamics/function relationship. In the last few years, we demonstrated the importance of Molecular Dynamics (MD) simulations coupled to experiments in describing and predicting the atomistic behavior of DNA nanoswitches [26,27] integrated into complex nanostructures [28]. Recently, it was experimentally shown that the pH-responsive behavior of a nucleic acid nanoswitch, which can form an intramolecular triplex structure through hydrogen bonds (Hoogsteen interactions) between a hairpin double helix (DH) and a single-strand triplex-forming oligo (TFO) with two protonation centers, strongly depends on the length of the linker connecting the two domains (Figure 1A) [29].…”
Section: Introductionmentioning
confidence: 99%